Transcriptomics Analysis of Circular RNAs Differentially Expressed in Apoptotic HeLa Cells - Yaylak, Bilge; Erdogan, Ipek; Akgul, Bunyamin (Frontiers in Genetics, 2019)
Apoptosis is a form of regulated cell death that plays a critical role in survival and developmental homeostasis. There are numerous reports on regulation of apoptosis by protein-coding genes as well as small non-coding RNAs, such as microRNAs. However, there is no comprehensive investigation of circular RNAs (circRNA) that are differentially expressed under apoptotic conditions. We have performed a transcriptomics study in which we first triggered apoptosis in HeLa cells through treatment with four different agents, namely cisplatin, doxorubicin, TNF-alpha and anti-Fas mAb. Total RNAs isolated from control as well as treated cells were treated with RNAse R to eliminate the lineer RNAs. The remaining RNAs were then subjected to deep-sequencing to identify differentially expressed circRNAs. Interestingly, some of the dys-regulated circRNAs were found to originate from protein-coding genes well-documented to regulate apoptosis. A number of candidate circRNAs were validated with qPCR with or without RNAse R treatment as well. We then took advantage of bioinformatics tools to investigate the coding potential of differentially expressed RNAs. Additionally, we examined the candidate circRNAs for the putative miRNA-binding sites and their putative target mRNAs. Our analyses point to a potential for circRNA-mediated sponging of miRNAs known to regulate apoptosis. In conclusion, this is the first transcriptomics study that provides a complete circRNA profile of apoptotic cells that might shed light onto the potential role of circRNAs in apoptosis.